Toxicity and application of neem in fall armyworm - Silva, Marcílio Souza; Broglio, Sônia Maria Forti; Prédes Trindade, Roseane Cristina; Ferrreira, Emerson Santos; Gomes, Ismael Barros; Micheletti, Lígia Broglio (Comunicata Scientiae, 2015)
Aqueous extracts of neem, Azadirachta indica A. Juss., leaf and seed cake were tested for toxicity in Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) utilizing different methods of application (foliar and systemic). Probit analysis was used to determine the LC50 and regression analysis for mortality at different concentrations of the extracts (0.5%, 1.0%, 1.5%, 2.0% and control treatment). Two caterpillar morphometric variables (larval length and cephalic capsule width) and the scale of damage of attacked plants were measured and, analyzed using the Kruskal-Wallis test (P<0.05). The LC50 values for neem seed cake and leaves were 0.13% and 0.25%, respectively. For larval length and cephalic capsule width, the larvae were more affected to the seed cake extract than leaf extract, however there was no significant difference between the methods of application for these variables. There was no difference in the scale of damage by the extracts and the methods of application analyzed. Both methods of application provided similar results and, the main differences were associated with more efficient of the seed cake extract.